ChemInform Abstract: An Asymmetric Organocatalytic Quadruple Domino Reaction Employing a Vinylogous Friedel—Crafts/Michael/Michael/Aldol Condensation Sequence. Issue 52 (10th December 2015) - Philipps, Arne R.; Fritze, Lars; Erdmann, Nico; Enders, Dieter
Abstract: Highly functionalized cyclohexenecarbaldehydes bearing a 1, 1‐bis[4‐(dialkylamino)phenyl]ethene moiety and three contiguous stereogenic centers are synthesized with very good diastereoselectivity, virtually complete enantiomeric excess, and good functional group tolerance.